2021
DOI: 10.1371/journal.pone.0259749
|View full text |Cite|
|
Sign up to set email alerts
|

Silicon-based induced resistance in maize against fall armyworm [Spodoptera frugiperda (Lepidoptera: Noctuidae)]

Abstract: The fall armyworm (Spodoptera frugiperda) is a major economic pest in the United States and has recently become a significant concern in African and Asian countries. Due to its increased resistance to current management strategies, including pesticides and transgenic corn, alternative management techniques have become more necessary. Currently, silicon (Si) is being used in many pest control systems due to its ability to increase plant resistance to biotic and abiotic factors and promote plant growth. The curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The larvae of the pest bore into grains and consume endosperms; thus, making seeds unfit for consumption and germination [ 25 ]. The pupae develop inside the grains, while adults emerge through grain holes [ 16 ]. The C .…”
Section: Introductionmentioning
confidence: 99%
“…The larvae of the pest bore into grains and consume endosperms; thus, making seeds unfit for consumption and germination [ 25 ]. The pupae develop inside the grains, while adults emerge through grain holes [ 16 ]. The C .…”
Section: Introductionmentioning
confidence: 99%
“…This causes an resistance to herbivores through the physical and biochemical mechanisms [36,37] and affect the development of herbivore [38]. Haq et al [39] reported that FAW fed on maize treated with Si showed a significant negative effect on various biological parameters of FAW. Insect ingested silicon will cause midgut epithelium of the yellow stem borer, Scirpophaga incertulas Walker (Lepidoptera: Crambidae), was completely ruptured the peritropic membrane and columnar cell and release of cell granules into the lumen due to abrasion of the midgut epithelium of larvae [35].…”
Section: Effect Of Biosilica Fertilizer On Plant Damage By Fawmentioning
confidence: 99%
“…To date, research on the response of host plants to S. frugiperda were focused on plant volatile compound identification, genetic resistance, host plant preference, etc. (Costa et al, 2020;De Lange et al, 2020;Garlet et al, 2021;Hafeez et al, 2021;Haq et al, 2021;Jacques et al, 2021;Lv et al, 2021;Murad et al, 2021;Yactayo-Chang et al, 2021;Peterson et al, 2022). However, the performance and the mechanism of maize plants in response to S. frugiperda still need to be studied further.…”
Section: Introductionmentioning
confidence: 99%